Spatiotemporal Evolution and Multilevel Driving Mechanisms of Water Ecological Health in the Lixiahe Plain River Network: A DPSIRM-Based Framework for Sustainable Development - Tian Cheng; Geng Niu; Guanhang Sui; Tianchi Duan; Yu Zhang; Yue Xin; Junxian Yin (Sustainability, 2026)
Maintaining water ecological health is essential for the sustainable development of plain water-network regions, where natural hydrological conditions and intensive human activities jointly shape ecological processes. To address the limited understanding of driving pathways, system-level contributions, and key internal factors affecting water ecological health, this study focused on the Lixiahe Plain, a typical plain water-network region in China. A water ecological health assessment system was developed based on the DPSIRM framework, and the Water Ecological Health Index (WEHI) was calculated at a 1 km grid scale from 2000 to 2020. PLS-SEM, RDA-VPA, and XGBoost-SHAP were further integrated to identify subsystem pathways, independent and interactive explanatory contributions, and key driving factors. The results showed that WEHI exhibited an overall fluctuating upward trend, increasing from 0.541 in 2000 to 0.594 in 2020, with the lowest value of 0.511 observed in 2010. Spatially, high-WEHI areas were mainly distributed in the southern and central–eastern regions and gradually expanded. PLS-SEM revealed stage-dependent differences in the direction and magnitude of subsystem effects, with the explained variance increasing from 21.7% in 2010 to 70.9% in 2020. The state and impact subsystems were the main carriers of WEHI variation. XGBoost-SHAP further identified vegetation coverage, RSEI, and soil moisture as key explanatory factors. The integrated results reveal the multilevel mechanisms underlying water ecological health in the Lixiahe Plain and provide a scientific basis for spatially differentiated ecological restoration and sustainable water and ecosystem management in plain water-network regions.